Relationship between Ca2+ and cAMP as second messengers in ACTH-induced cortisol production in bovine adrenal fasciculata cells - Masahiko Kutsukake; Naoko Kuwabara; Yoshikazu Miyate; Kenzo Kudo; Shoko Goto; Eiichi Taira; Eiichi Tachikawa (Endocrine Journal)
In adrenal fasciculata cells stimulated by ACTH, Ca2+ and cAMP play indispensable roles as second messengers in cortisol production. However, whether their second messengers cooperatively or independently participate in steroid production remains unclear. We focused on the roles of Ca2+ and cAMP in cortisol production in bovine adrenal fasciculata cells stimulated by ACTH for a relatively short period (1 h). Incubation of the cells with 100 pM ACTH in Ca2+-containing (normal) medium for 1 h increased cortisol production without affecting cAMP content. In contrast, treatment of the cells with the peptide at a higher concentration (1 nM) significantly augmented both cortisol production and cAMP content. However, ACTH did not increase either of them in the Ca2+-free medium. ACTH rapidly increased the intracellular free Ca2+ concentration ([Ca2+]i) in the normal medium, but did not influence [Ca2+]i in the Ca2+-free medium, indicating that ACTH caused Ca2+ influx into the cells. ACTH-induced Ca2+ influx and cortisol production were suppressed by a voltage-sensitive L-type Ca2+ channel blocker but not by a T-type, N-type, or P-type Ca2+ channel blocker. In contrast, dibutyryl cAMP, a cell-permeable cAMP analog, greatly enhanced cortisol production in the normal or Ca2+-free medium and slowly caused Ca2+ influx into the cells. These results strongly suggest that Ca2+, as a second messenger, is more critical than cAMP for cortisol production. However, both second messengers jointly participate in the production in adrenal fasciculata cells stimulated by ACTH.